Indicadores de Calidad en Leche de Tanque de Cinco Fincas del Municipio de Popayán, Cauca. (2023)
Quality parameters in milk are a key issue for both the dairy industry and consumer health. This study examines key indicators that include the physicochemical composition of milk, such as its fat content, proteins, total solids and somatic cell count, which directly affects its nutritional value and organoleptic properties. The objective of this study was to evaluate the quality parameters of raw milk in five cooling tanks in the municipality of Popayán, Cauca. Samples were collected from five tanks at 30-day intervals, and parameters such as bacteria, physicochemical quality and somatic cell count were analyzed. Microbiological parameters showed a greater presence of Enterobacteriaceae type bacteria such as Klebsiella pneumoniae with an average percentage of 50%, 37.5% corresponded to Citrobacter freundii and 12.5% to Escherichia coli. In terms of physicochemical quality, the average fat in the samples of the five farms was 61.97%, the average protein 46.971%, total solids 197.74% and somatic cell count 6.635.846%. Finally, the presence of microorganisms is evidenced in the milk samples of the five cooling tanks, which generate a degradation since milk is a product sensitive to the proliferation of microbiological agents by antibiotic resistance, also influence compositional quality and nutritional use, implying an impact on public health